Bullying and peer violence among children and adolescents in residential care settings: A review of the literature. (January 2018) - Mazzone, Angela; Nocentini, Annalaura; Menesini, Ersilia
Abstract: The present paper offers a review of the phenomena of bullying and peer violence among children and adolescents living in residential care settings (RCS). The review was conducted on four databases (Scopus, Web of Science, PsycINFO and ERIC). Findings of the 31 full-text papers included in the present work showed that bullying and peer violence involve various forms of direct and indirect attacks. While bullying in RCS involves severe and repeated aggressive actions, peer violence seems to be characterized by distinct levels of severity; i.e., low-level attacks are infrequent and isolated, whereas high level attacks may be severe and frequent. Several individual factors, such as age, gender, and length of stay in RCS were found to be associated with both bullying and peer violence. Contextual risk factors such as activities, structure and facility size, along with a residential peer culture characterized by a high level of hierarchy and a poor emotional bond between children and staff, contributed to bullying and peer violence. Furthermore, findings of the studies included in the present review showed that both perpetrators and victims manifest a number of behavioral and psychological problems. Overall, the present study offers a picture of bullying and peer violence among institutionalized children. However, distinct operationalization of constructs among studies, together with the use of different methods and measures, made comparisons among studies difficult. Future research should overcome these limitations in order to promote validity and compatibility of research in this field of study. Highlights: A review of bullying and peer violence in residential care was conducted. Bullying and peer violence among institutionalized children are wide-spread phenomena. Peer hierarchies are associated with bullying and peer violence. Poor social bond with professionals and anti-grassing culture increase bullying and peer violence. Poly victimization increases the risk for behavioral and psychological problems.